When Corporate Social Responsibility (CSR) Meets Organizational Psychology: New Frontiers in Micro-CSR Research, and Fulfilling a Quid Pro Quo through Multilevel Insights - Jones, David A.; Willness, Chelsea R.; Glavas, Ante (Frontiers in Psychology, 2017)
Researchers, corporate leaders, and other stakeholders have shown increasing interest in Corporate Social Responsibility (CSR)—a company’s discretionary actions and policies that appear to advance societal well-being beyond its immediate financial interests and legal requirements. Spanning decades of research activity, the scholarly literature on CSR has been dominated by meso- and macro-level perspectives, such as studies within corporate strategy that examine relationships between firm-level indicators of social/environmental performance and corporate financial performance. In recent years, however, there has been an explosion of micro-oriented CSR research conducted at the individual level of analysis, especially with respect to studies on how and why job seekers and employees perceive and react to CSR practices. This micro-level focus is reflected in 12 articles published as a Research Topic collection in Frontiers in Psychology (Organizational Psychology Specialty Section) titled “Corporate social responsibility and organizational psychology: Quid pro quo.” In the present article, the authors summarize and integrate findings from these Research Topic articles. After describing some of the “new frontiers” these articles explore and create, the authors strive to fulfill a “quid pro quo” with some of the meso- and macro-oriented CSR literatures that paved the way for micro-CSR research. Specifically, the authors draw on insights from the Research Topic articles to inform a multilevel model that offers multiple illustrations of how micro-level processes among individual stakeholders can explain variability in meso (firm)-level relationships between CSR practices and corporate performance. The authors also explore an important implication of these multilevel processes for macro-level societal impact.